2015
DOI: 10.1186/s40734-014-0011-2
|View full text |Cite
|
Sign up to set email alerts
|

Freezing of gait and white matter changes: a tract-based spatial statistics study

Abstract: BackgroundWe hypothesized that the integrity of white matter might be related to the severity of freezing of gait in age-related white matter changes.MethodsTwenty subjects exhibiting excessive hyperintensities in the periventricular and deep white matter were recruited. The subjects underwent the Freezing of Gait Questionnaire, computerized gait analyses, and diffusion tensor magnetic resonance imaging. Images of axial, radial and mean diffusivity, and fractional anisotropy were calculated as indices of white… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…Among 429 non-demented later middle-aged adults (mean age=65) with cerebral small vessel disease, lower FA and higher MD of the corpus callosum was associated with slower gait speed, reduced stride length and cadence, and increased stride width [23]. In a smaller study of 20 older adults (range=65–84) with significant cerebrovascular pathology, lower FA and higher MD, and axial and radial diffusivity across all WM were associated with freezing of gait [24]. Another study that examined the effect of FA within the context of WMHs found that FA measures throughout WM regions significantly moderated the association between WMH volume and gait speed among 265 community-dwelling older adults (mean age=83) [25].…”
Section: White Matter (Wm)mentioning
confidence: 99%
“…Among 429 non-demented later middle-aged adults (mean age=65) with cerebral small vessel disease, lower FA and higher MD of the corpus callosum was associated with slower gait speed, reduced stride length and cadence, and increased stride width [23]. In a smaller study of 20 older adults (range=65–84) with significant cerebrovascular pathology, lower FA and higher MD, and axial and radial diffusivity across all WM were associated with freezing of gait [24]. Another study that examined the effect of FA within the context of WMHs found that FA measures throughout WM regions significantly moderated the association between WMH volume and gait speed among 265 community-dwelling older adults (mean age=83) [25].…”
Section: White Matter (Wm)mentioning
confidence: 99%
“…34,35 Principally, freezing of gait is found in patients with WM lesions, and has been associated with disintegration of microstructures in the striato-frontal WM. 36,37…”
Section: Symptomatic Heterogeneity In Patients With Wm Lesionsmentioning
confidence: 99%
“…On the other hand, parkinsonian gait disorder has been attributed to frontal WM lesions . Principally, freezing of gait is found in patients with WM lesions, and has been associated with disintegration of microstructures in the striato‐frontal WM …”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of FOG is complicated and involves multiple mechanisms, including disordered limbic system and cognitive functions regulated by the basal ganglia, supplementary motor area, and cerebral cortex (Iseki et al., ; Okuma, ; Snijders et al., ; Teramoto, Morita, Ninomiya, Shiota, & Kamei, ). The association of FOG with these systems has not yet been investigated in detail.…”
Section: Introductionmentioning
confidence: 99%